Comparison of recovery methods for the enumeration of injured Listeria innocua cells under isothermal and non-isothermal treatments - Miller, Fátima A. (2011)
This study compares the feature of different media with the combination of selective with non-selective media in a TAL method for recovery of Listeria innocua cells exposed to thermal treatments. Experiments were conducted in broth at constant temperature (52.5 and 65.0 ºC) and pH (4.5 and 7.5) conditions, using NaCl or glycerol to adjust water activity to 0.95. Four different media were used in bacterial cell enumeration: (i) a non-selective medium e TSAYE, (ii) two selective media e TSAYE þ 5%NaCl and Palcam Agar and (iii) TAL medium (consisting of a layer of Palcam Agar overlaid with one of TSAYE). Two food products were used as case studies aiming at comparison of results obtained on selective and TAL media enumeration. Parsley samples were inoculated with L. innocua and subjected to posterior thermal treatments both under isothermal (52.5, 60.0 and 65.0 ºC) and non-isothermal (heating rate of 1.8 ºC/min from 20.0 to 65.0 ºC) conditions. The recovery capability of TAL method was also studied when a pre-cooked frozen food (i.e. meat pockets) was fried (oil temperature of w180 ºC). TAL method proved to be better than Palcam Agar in terms of capability to recover injured cells and was effective in L. innocua enumeration when non-sterile samples were analysed.